Contribution of Commitment to Duties and Provision of Rewards to the Work Discipline of Teachers of State Junior High Schools in East Binjai District - Candra Wijaya; Edi Saputra; Yenni Fitri (EDUTEC : Journal of Education And Technology, 2022)
This study aims to reveal: 1) The contribution of commitment to the work discipline of State Junior High School teachers in East Binjai District, 2) The contribution of giving rewards to the work discipline of Public Junior High School teachers in East Binjai District, and 3) The contribution of work commitment and mutual reward on the discipline of state junior high school teachers in East Binjai District. This study uses simple and multiple regression statistical analysis techniques with a sample of 42 teachers. Data collection techniques were obtained through a questionnaire. The findings of this study reveal that there is a significant and meaningful contribution between commitment to assignments and teacher work discipline. This means that the higher and positive the commitment to the task, the higher and positive the work discipline of SMP Negeri teachers in East Binjai District by providing an effective contribution of 14.3%. This means that the variation that occurs in the commitment variable to the task of 14.3% can be predicted in improving teacher work discipline; there is a significant and meaningful contribution to the provision of rewards to the work discipline of teachers. This means that the higher and more positive the reward, the higher and positive the work discipline of SMP Negeri teachers in East Binjai District by providing an effective contribution of 14.2%. This means that the variation that occurs in the variable reward of 14.2% can be predicted in improving teacher work discipline; and there is a significant and meaningful contribution to the commitment to the task and the joint provision of rewards to the teacher's work discipline. This means that the higher and positive the commitment to the task and the provision of rewards together, the higher and positive the work discipline of SMP Negeri teachers in East Binjai District by providing an effective contribution of 14.7%. This means that the variation that occurs in the variable of commitment to the task and the provision of rewards together of 14.7% can be predicted in improving teacher work discipline.